ENERGY LOADING OF MULTI-CHAMBER PULLEYS OF BAND-SHOE BRAKES OF DRILL WINCHES - Кіндрачук, Мирослав; Бекіш, Ірина; Андрейчіков, Євгеній; Присяжний, Андрій; Нікіпчук, Сергій; Пороховський, Юрій (Problems of Friction and Wear, 2022)
The material of the article contains the following issues: design and operation of a self-cooled band-shoe brake; heat transfer through the cylindrical walls of a self-cooled pulley (boundary conditions of the ІІІ kind); discussion of the results. Development and investigation of the design of a self-cooled pulley brake to reduce its energy load due to forced nano-fluid independent cooling of the pulley elements. A scheme of a thermal model of a tribosystem with an air-nano-liquid cooling system for friction pairs of a band-shoe brake is proposed. Homogeneous cylindrical walls with outer and inner diameters are considered in the middle part of which there are horizontal independent chambers connected to the vertical chambers of the left and right flanges, as well as to a non-metallic fastening ledge. The coefficient of thermal conductivity of the material is constant self-cooling pulley. Nanofluid was used as a heat carrier in the chambers, which corresponded to the operating conditions of the friction pairs of the brake. The linear heat transfer coefficients between the first, second, and third horizontal chambers are determined, taking into account the energy load of the vertical chambers of the left and right flanges, as well as the pulley mounting lug. Regularities of change in thermal resistance of thermal conductivity (Rλ) and heat flux (q) penetrating the walls of the first chamber from its diameters are established. With respect to the third horizontal chamber, the thickness of its walls does not play a role in heat transfer, since it is connected to the vertical chamber of a non-metal-intensive fastening ledge of the pulley, which has a small metal content.